Trends in Peripheral Nerve Block Usage in Mastectomy and Lumpectomy: Analysis of a National Database From 2010 to 2018. (July 2021) - Lam, Stephanie; Qu, Helena; Hannum, Margaret; Tan, Kay See; Afonso, Anoushka; Tokita, Hanae K.; McCormick, Patrick J.
Abstract : BACKGROUND: Compared to general anesthesia, regional anesthesia confers several benefits including improved pain control and decreased postoperative opioid consumption. While the benefits of peripheral nerve blocks (PNB) have been well studied, there are little epidemiological data on PNB usage in mastectomy and lumpectomy procedures. The primary objective of our study was to assess national trends of the annual proportion of PNB use in breast surgery from 2010 to 2018. We also identified factors associated with PNB use for breast surgery. METHODS: We identified lumpectomy and mastectomy surgical cases with and without PNB between 2010 and 2018 using the Anesthesia Quality Institute National Anesthesia Clinical Outcomes Registry (AQI NACOR). We modeled the nonlinear association between year of procedure and PNB use with segmented mixed-effects logistic regression clustered on facility identifier. The association between PNB use and year of procedure, age, sex, American Society of Anesthesiologists physical status (ASA PS), facility type, facility region, weekday, and tissue expander use was also modeled using mixed-effects logistic regression. RESULTS: Of the 189, 854 surgical cases from 2010 to 2018 that met criteria, 86.2% were lumpectomy cases and 13.8% were mastectomy cases. The proportion of lumpectomy cases with PNB was <0.1% in 2010 and increased each subsequent year to 1.9% in 2018 (trend P < .0001). The proportion of mastectomy cases with PNB was 0.5% in 2010 and 13% in 2018 (trend P < .0001). The year 2014 was the breakpoint selected for segmented regression. Before 2014, the odds of PNB among the mastectomy cases was not significantly different from year to year. After 2014, the odds of PNB increased by 2.24-fold each year (95% confidence interval [CI], 2.00–2.49; P < .001); interaction test for pre-2014 versus post-2014 was P < .001. Similar trends were seen in the lumpectomy cases, where after 2014, the odds of PNB increased by 2.03-fold (95% CI, 1.81–2.27; P < .001); interaction test for pre-2014 versus post-2014 was P < .001. In the mastectomy cohort, year of procedure ≥2014, female sex, facility region, and tissue expander use were associated with higher odds of PNB. For lumpectomy cases, year of procedure ≥2014 and facility region were associated with higher odds of PNB use. CONCLUSIONS: We found increased annual utilization of PNB for mastectomy and lumpectomy since 2010, although absolute prevalence is low. PNB use was associated with year of procedure for both lumpectomy and mastectomy, particularly post-2014.